Solidarność Walcząca . tygodnik organizacji Solidarność Walcząca Oddz. Poznań, no. 161, 1990 - [ed. committee] (Agencja Informacyjna Solidarności Walczącej [various acronyms], 1990)
Creation and circulation: From issue no. 16=232(1990) published legally titled Solidarność Walcząca : kwartalnik polityczny. Issue no. 16 is the consequtive numer of the Poznań edition of Solidarność Walcząca, no. 232 is the consequtive number of Solidarność Walcząca perviously published in Wrocław